PENGEMBANGAN SISTEM INFORMASI BUKU INDUK SISWA BERBASIS WEB DI SMP MUHAMMADIYAH 2 LENDAH - Tsabita, Latifah; Surjono, Herman Dwi (Department of Electronics and Informatics Engineering Education, 2024)
The purpose of this research are: (1) develop a web-based student registry information system to manage student data at SMP Muhammadiyah 2 Lendah, and (2), to conduct quality testing of the developed system using ISO 25010 standards related to functional suitability and usability. This research was conduct at SMP Muhammadiyah 2 Lendah. This research used the Research and Development (R&D) method, the waterfall model for the development process and descriptive quantitative for data analysis. The waterfall model consists of five stages, the requirements analysis stage produces a list of system functional requirements and device requirements. The system design stage produces architecture design, database design, and user interface design. The implementation and unit testing stage yield system development using the CodeIgniter framework, with each unit being tested. The integration stage produces a system ready for use, and the system testing stage using the ISO 25010 standards, focusing on functional suitability aspect evaluated by 2 expert and usability aspect evaluated by 15 respondents. The operation and maintenance stage involves delivering the system to SMP Muhammadiyah 2 Lendah. This research resulted in a web-based student registry information system used for managing student data at SMP Muhammadiyah 2 Lendah. The functional suitability testing yielded a 100% score, indicating it is highly suitable. Usability testing resulted in a score of 71,5, which places the system in the “Good” category, suggesting that users may need some learning to utilize it effectively.